Effect of Curing Temperature on the Properties of Latex Based Membrane for Oily Wastewater Filtration. Issue 1 (December 2021) - Yong, Tzyy-Jeng; Munusamy, Yamuna; Ong, Yit-Thai; Yeoh, Wei-Ming; Kchaou, Mohamed
Abstract: Oily wastewater pollution has always been part of the most serious worldwide environmental disaster. Thus, the treatment of oily wastewater is notably crucial. In this work, nitrile butadiene rubber/graphene oxide (NBR/GO) membranes were fabricated by latex compounding and curing method which is comparatively brand-new technique to produce membranes for wastewater treatment. Therefore, the steps in the production need to be studied to enhance the performance of the membrane. Curing temperature is an important factor in the production of the latex-based membrane. In this paper, the effect of curing temperature in the range of 90 °C – 110 °C on the morphology, tensile properties, permeation flux, and oil rejection rate performance of the membrane was studied. The curing temperature was found to affect the surface morphology and integrity of the membranes which sequentially affects the performance of the membrane in terms of strength, permeation flux, and oil rejection rate. NBR/GO membranes cured at the temperature of 100 °C exhibit the highest flux of 491.84 L/m2.hr with an oil rejection rate of 95.44 %, with the ultimate tensile strength (UTS), elongation break (EB%), and E-Modulus (E-mod) of 34.490 MPa, 1627.11 %, and 1.309 MPa, respectively.